PENERAPAN AKAD MURABAHAH DALAM PRODUK GADAI EMAS BANK SYARIAH MANDIRI (BSM) DI KANTOR CABANG SLEMAN - Renny Tri Setiani (Kajian Hukum, 2018)
Islamic Pawn Gold is the product that created by Bank Syariah Mandiri since March, 25 2013 which the gold belongs to the customer. Islamic Pawn Gold gives the chance for people to own the bar gold by buying the gold by credit under murabahah aggreement with the guarantee rahn and the minimal of gold is 10-250 gram. National Council of Ulama Indonesia has created the fatwa related to Pawn Gold no 77/DSNMUI/V/2010 about selling buying of gold without cash. BSM uses this moment to fulfill the needs of people to invest. In this research appears the problem of whether the Murabahah aggrement and Rahn aggreement which applied by BSM Sleman about pawn gold appropriate with Syariah principal. The ethod used in this research is Normatif researh or Doctrinal Research by Juridical Normatif approach. While the data is secinder data, those are primer data, secondery data, tertiary data. Library research used to collect the data by examining library data as the base of qualitative analysis. The research concludes that Murabahah aggrement which applied by BSM Sleman about pawn gold has appropriated with Syariah principal which free from Riba, save from gamble (Maysir) and syubhat. That principal based on An-Nisa  ayat  29  and  Al-Hadist  of  H.R  Ibnu  Maja dan Fatwa DSN MUI 77/DSN-MUI/V/2010 about pawn gold without cash. In other condition, several customers do not show thei gold physically. This condition contradict with syariah principal and make the condition unclear (gharar). And Rahn aggreement which applied by BSM Sleman about pawn gold has appropriated with Syariah principal. Meanwhile, the wrong Murabaha agreement application will affect the Rahn agreement as well.Keywords: Syariah Pawn Gold, Bsm kcp sleman, murabaha agreement.